2016
DOI: 10.5572/kosae.2016.32.1.082
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Domestic and Foreign Contributions using DDM in CMAQ during Particulate Matter Episode Period of February 2014 in Seoul

Abstract: This study was carried out to understand the regional contribution of Particulate Matter (PM) emissions from East Asia (82°~149°E, 18°~53°N) to Seoul during high concentration period in February 2014.The Community Multi-scale Air Quality (CMAQ) version 5.0.2 with Decoupled Direct Method (DDM) was used to analyze levels of contributions over Seoul. In order to validate model performance of the CMAQ, predicted PM and its chemical species concentrations were compared to observations in China and Seoul. Model pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 23 publications
3
8
0
Order By: Relevance
“…Especially, the 10-m wind speeds were overestimated in the winter by up to 0.8 m/s. We note that the overestimation of the wind speeds was most pronounced in coastal regions ( Figure S4), which is consistent with the findings of Kim et al [32].…”
Section: Performance Evaluation Of the Wrf Simulationsupporting
confidence: 93%
See 1 more Smart Citation
“…Especially, the 10-m wind speeds were overestimated in the winter by up to 0.8 m/s. We note that the overestimation of the wind speeds was most pronounced in coastal regions ( Figure S4), which is consistent with the findings of Kim et al [32].…”
Section: Performance Evaluation Of the Wrf Simulationsupporting
confidence: 93%
“…Kim et al [6] reported that the foreign contribution to the annual mean PM 2.5 concentration for SMA comprised over 60% in 2014. The Chinese contribution to the PM 2.5 concentration for SMA in February 2014 was 40-50% during high PM 2.5 days [32] and reached up to 70% at the Bulgwang supersite in Seoul [32]. The range in the Chinese contribution estimated in this study is similar to the results of the previous studies mentioned earlier [5,6,30].…”
Section: The Chinese Contribution To the Pm25 Concentrations In The supporting
confidence: 88%
“…Using CMAQ simulation of January 2007, Koo et al (2008) demonstrated that PM 10 transport from China to South Korea is significant, contributing up to 80 % of total concentration during the studied period. Using the CMAQ Decoupled Direct Method (DDM), Kim et al (2016b) also concluded that PM 10 concentration in Seoul is mostly contributed from Chinese industrial and urban regions (39.8-53.2 %), emissions in South Korea (15.4-37.1 %), and emissions in North Korea (9.0-18.1 %). All these studies, however, have examined short, episodic periods, and/or have used a limited set of modeling configurations.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the contributions of fine dust domestically and from foreign countries in 2018 by NIER revealed that the average foreign contribution constituted about 44–55%, which is different from the 60–80% of high concentration of fine dust known to be contributed by foreign influences 6 . It is supported by the facts that much of fine dust generation is due to domestic factors that are a continuation of domestic high pressure impact and stagnation of Barometer 7 , increased direct air pollutant emissions domestically 8 , 9 , and difference between measurement sites due to emitted air pollutants cannot move away 10 even if high concentration fine dust in the windward area such as Chinese Bohai region formed the inflow route to the South Korea (domestic) by the northwest wind 11 , 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%